NOMADISM AND ADAPTATIONS TO SEDENTARY LIFESTYLES AMONG THE EVENKI OF POST-SOVIET SIBERIA: "PLAYING" TO LIVE WITH AND WITHOUT SHAMANS - Lavrillier, Alexandra (HAL CCSD, 2005)
The Evenki oročon live in Yakutia (Sakha Republic) and in the Amur basin. They perceive themselves as an integral part of the natural environment. They were partly sedentarized under the Soviet regime, and they are now to get to the market economy. They can be divided into three social types: nomadic reindeer-breeders and hunters, villagers, and city dwellers. The analysis of the different lifestyles, forms of organization, individual distinctive factors and inherited values allows us to determine the place and functions of the ritual practices and of the types of ritual specialists in every social type.The main result of this thesis, based on five-year fieldwork, is a comparative analysis of rituals. The author compares the rituals she observed among the nomads with those described in the sources of the Soviet period on the one hand, and with those she observed among sedentary people on the other hand. While certain individual and collective rituals described in ethnographic literature have disappeared, the traditional system of representation remains, as an unconscious knowledge that underlies new rituals and multiple prohibitions. The nomads follow their ancestors’ models, while villagers and city-dwellers multiply the modes of representation within one and the same event. These modes of representation include fragments of traditional rituals, theatrical stagings of forgotten rituals and shamans, audiovisual documents. A new category thus appears, that of “rituals that represent rituals”. The nomads prefer not to carry out the rituals whose procedure they do not know for sure, for they fear to send their “soul” out of “the world of the living” in case of making mistake. As for the sedentary intellectuals, they boldly “reinvent” rituals, maintaining that the spirits would appreciate the humans’ care for them and know how to express their gratitude. The comparison also shows that a distinction between sacred and profane has appeared. Likewise, we should establish a distinction between an “unconscious tradition” ...